PENGARUH KOMUNIKASI KELUARGA TERHADAP KREATIVITAS BELAJAR SISWA SMP NEGERI 19 BEKASI PROVINSI JAWA BARAT - Afrina Sari (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
The aims of this study are to: 1) analyze the form of student creativity in SMP Negeri 19 Bekasi in academic year 2009/2010. 2) analyze the influence of family communication on student creativity in SMP Negeri 19 Bekasi in academic year 2009/2010? 3) find factors affecting student creativity in SMP Negeri 19 Bekasi in academic year 2009/2010. Sampling technique using proportional stratified random sampling method produces 62 samples. Data were analyzed using frequency analysis, the percentage also use the regression test of inferential statistics, normality tests. The results showed that 1) the intensity communication of the student family who study in SMP Negeri 19 Bekasi in academic year 2009/2010 includes both categories with the percentage of 64.47%. 2) Student creativity in SMP Negeri 19 Bekasi in academic year 2009/2010 is categorized by percentage 62.29%. 3) There is a positive influence on the intensity of family communication creativity in SMPN 19 Bekasi in academic year 2009/2010. The amount of influence on the intensity of the family communication creativity lessons learning student of the academic year 2005/2006 amounted to 42.4%.